Cytokines Driven Anti-Inflammatory and Anti-Psoriasis Like Efficacies of Nutraceutical Sea Buckthorn (Hippophae rhamnoides) Oil - Acharya Balkrishna; Acharya Balkrishna; Sachin Shridhar Sakat; Kheemraj Joshi; Kamal Joshi; Vinay Sharma; Ravikant Ranjan; Kunal Bhattacharya; Anurag Varshney; Anurag Varshney (Frontiers Media S.A., 2019)
Psoriasis is a chronic inflammatory skin disease characterized by circumscribed, red, thickened plaques with overlying silvery white scales. It is associated with the release of pro-inflammatory mediators that lead to the development of edema and distress. Here we show the anti-inflammatory and anti-psoriatic efficacies of a neutraceutical sea buckthorn oil (SBKT) derived from the fruit pulp of Hippophae rhamnoides. Chemical analysis of the SBKT showed the presence of 16 major saturated, mono-, and polyunsaturated fatty acids components, imparting significant nutritional values. Efficacy of the SBKT in modulating psoriasis and associated inflammation was first tested in vitro using human monocytic (THP-1) cells. SBKT induced cytotoxicity at a dose of ≥25 µl/ml. Treatment of the lipopolysaccharide-stimulated THP-1 cells with SBKT subdued the enhanced release of intracellular reactive nitrogen species and expression of NF-κB protein, in a concentration-dependent manner. This was accompanied by a reduction in the release of downstream pro-inflammatory cytokines: Interleukin-1ß and interleukin-6. Tumor necrosis factor-α released in the stimulated THP-1 cells were also inhibited by SBKT dose of 5 µl/ml. In vivo oral and topical treatment with SBKT in the Carrageenan-stimulated paw edema model, showed a significant decrease in paw volume and edema. In the 12-O tetradecanoyl phorbol 13-acetate (TPA) stimulated CD-1 mice psoriasis-like model, concurrent oral and tropical SBKT treatments substantially reduced ear edema and ear biopsy weights. Histopathologically, significant reduction in ear epidermal thickness and skin lesion scores was observed in the SBKT-treated animals. In conclusion, SBKT showed anti-inflammatory and anti-psoriasis-like efficacies in healing chemical-induced inflammation and psoriasis. The possible mode of action of SBKT was found through inhibition of reactive nitrogen species, and downregulation of NF-κB protein and pro-inflammatory cytokines. Thus, the present data suggest that Sea buckthorn oil can be used as an anti-inflammatory and anti-psoriatic nutraceutical.